Immune Monitoring of Paediatric Patients Infected with Rickettsia rickettsii, Ehrlichia canis and Coinfected - Escarcega Avila, Angelica Maria (2022)
Abstract: In 2021, 273 Rocky Mountain spotted fever cases were reported nationwide in Mexico. In Chihuahua City, fourteen samples were obtained from children suspected of rickettsial infection. The analysis of samples (January to December 2021) showed prevalence rates of 28.5%, 43%, and 28.5% for Rickettsia rickettsii, Ehrlichia canis, and both pathogens in coinfection, respectively. The analysis of clinical haematological and biochemistry analytes showed alterations; 100% of the children had elevated liver enzymes and coagulation times, 64% showed leukocytosis due to neutrophilia, 55% had thrombocytopenia, lymphopenia, and hypoalbuminemia, and 45% showed normocytic normochromic anaemia. Statistically significant differences were observed in the expression of the chemokines IL-8, RANTES, CXCL9/MIG, and CXCL10/IP-10 across the coinfected and control groups, and the difference in IP-10 expression was significant for patients infected by R. rickettsii compared to the control group. Additionally, significant differences were observed for expression levels of IL-1β, IL-6, IL-17, IFNγ, and TNFα among the R. rickettsii-positive group compared to the control group. On the other hand, the coinfected group exhibited modified levels of IL-6, IL-8, and IL-10 compared with the control group. Finally, significant differences were observed for CD8+ T lymphocyte subpopulations between individuals positive for R. rickettsii and those positive for E. canis